Innovative Strategies Using Digital Technologies to Enhance Performance in Racket Games - Hussein, Ameera Sabry; Kadhim, Mayasa Abd Ali; Aldewan, Lamyaa Hasan; Ghazi, Mohammed Asim (CV. Abhinaya Indo Group, 2025)
This study examines the impact of innovative strategies using digital technologies on enhancing performance in racket games, such as badminton and table tennis. An experimental approach was used on a sample of 50 students from the fourth stage in colleges of physical education. The sample was divided into two groups: an experimental group that used digital strategies and a control group that used traditional methods. The results showed a statistically significant positive relationship between the use of digital technologies and the players' performance in badminton, where p-value = 0.021. The results also showed that the group that used digital technologies was superior in the level of technical skills, with a p-value = 0.005 in shot accuracy and 0.012 in speed. The results indicate that digital technologies enhance physical and mental performance, which calls for their integration into training programs.